2008
DOI: 10.1093/ndt/gfm847
|View full text |Cite
|
Sign up to set email alerts
|

Preventing haemodialysis catheter-related bacteraemia with an antimicrobial lock solution: a meta-analysis of prospective randomized trials

Abstract: Background. Catheter-related bacteraemia (CRB) is a major cause of morbidity and mortality in haemodialysis patients. Interdialytic locking of catheters with antimicrobial agents has recently been investigated for the prevention of CRB. We performed a meta-analysis of randomized controlled trials (RCT) to determine the efficacy of antimicrobial lock solutions (ALS) in the prevention of CRB in haemodialysis patients. Methods. We collected from Medline, Web of Science, the Cochrane Library and major nephrology j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
95
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 31 publications
8
95
0
Order By: Relevance
“…James et al reported that the use of intraluminal antibiotics in 11 trials reduced the rate of catheter removal due to complication by 63% [79]. The meta-analysis of Labriola et al of nine trials documented that the use of AMLs in TCCs reduced the incidence of CRB by about a factor of three [80]. However, the achieved incidence of CRB in the ALS groups is similar to published reports from units with low CRB incidence (and presumably stricter hygienic measures) [80].…”
Section: B Preventing Contamination Of the Catheter Hubmentioning
confidence: 99%
See 2 more Smart Citations
“…James et al reported that the use of intraluminal antibiotics in 11 trials reduced the rate of catheter removal due to complication by 63% [79]. The meta-analysis of Labriola et al of nine trials documented that the use of AMLs in TCCs reduced the incidence of CRB by about a factor of three [80]. However, the achieved incidence of CRB in the ALS groups is similar to published reports from units with low CRB incidence (and presumably stricter hygienic measures) [80].…”
Section: B Preventing Contamination Of the Catheter Hubmentioning
confidence: 99%
“…The meta-analysis of Labriola et al of nine trials documented that the use of AMLs in TCCs reduced the incidence of CRB by about a factor of three [80]. However, the achieved incidence of CRB in the ALS groups is similar to published reports from units with low CRB incidence (and presumably stricter hygienic measures) [80]. Similarly, the meta-analysis of 11 studies by Yahav et al showed that the treatment of four patients with AMLs prevented one CRB [81].…”
Section: B Preventing Contamination Of the Catheter Hubmentioning
confidence: 99%
See 1 more Smart Citation
“…Boyce recently reviewed all antimicrobial lock studies (antibiotic-and non-antibiotic-based) performed from 1999 to 2012 and concluded that antimicrobial locks should be used for CRBSI prevention in all hemodialysis units (11). In addition, five meta-analyses or systematic reviews (12)(13)(14)(15)(16) published during this time period indicate significant reductions in CRBSI; in particular, two meta-analyses reported a number needed to treat to prevent one CRBSI of 3 to 4 (12,13). Most of the included studies compared an antimicrobial lock with heparin as the control and used different protocols for general catheter care, such that infection rates in the control groups were approximately 3 per 1000 catheter-days.…”
mentioning
confidence: 99%
“…Numerous randomized, controlled trials (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), as well as meta-analyses of these studies (21)(22)(23)(24)(25), have been performed during the past decade to evaluate the benefit of anti-microbial lock solutions in chronic hemodialysis patients with TCCs. These studies have been heterogeneous in nature and used different antibiotics (gentamicin, minocycline, cefazolin, cefotaxime, vancomycin) and nonantibiotic (citrate, taurolidine, EDTA) anti-microbial lock solutions; however, they have all shown a significant decline of 50 to 100% in CRIs compared with standard heparin lock without antibiotics or other sterilizing solutions (3).…”
mentioning
confidence: 99%